2012
DOI: 10.3109/08039488.2012.684703
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric disorders before and 1 year after bariatric surgery: The role of shame in maintenance of psychiatric disorders in patients undergoing bariatric surgery

Abstract: There was a significant reduction in prevalence of psychiatric disorders from pre-operative assessment to follow-up 1 year after surgery. Level of shame at pre-operative assessment was associated with maintenance of psychiatric problems. This finding is of clinical importance, since psychiatric disorders persisting after bariatric surgery have strong impact on the course of weight loss and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 46 publications
2
46
0
6
Order By: Relevance
“…However, a substantial proportion of people eligible for BS have a history of eating disorders or mental health problems [29,30]. Research looking at psychological predictors of obesity presents complex findings and is not well understood [31][32][33].…”
mentioning
confidence: 99%
“…However, a substantial proportion of people eligible for BS have a history of eating disorders or mental health problems [29,30]. Research looking at psychological predictors of obesity presents complex findings and is not well understood [31][32][33].…”
mentioning
confidence: 99%
“…On reading, it was found that 13 did not meet at least one criterion and the data of interest for this review were the same in two articles, 16,29 so the one with the earlier publication date was included and the later article was excluded 29 (Figure 1). At the end of this process, 16…”
Section: Methodsmentioning
confidence: 99%
“…Rates of clinical disorders (excluding personality disorders [PD] and mental deficiency) exceed 40% among candidates for BS [14][15][16] and psychiatric comorbidities are also evident. 15,16 Depressive, bipolar, anxiety, and eating disorders stand out as the most prevalent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations